2022
DOI: 10.1021/acs.oprd.1c00435
|View full text |Cite
|
Sign up to set email alerts
|

Citral-to-Menthol Transformations in a Continuous Reactor over Ni/Mesoporous Aluminosilicate Extrudates Containing a Sepiolite Clay Binder

Abstract: One-pot continuous synthesis of menthols from citral was performed over 5 wt % Ni supported on a mesoporous aluminosilicate catalyst with sepiolite as a binder at 70 °C with a selectivity of 75% to menthols. Catalyst deactivation with time-on-stream resulted in a decrease of the conversion and selectivity to menthols at the expense of higher selectivity to isopulegols. Stereoselectivity to isopulegols and menthols only slightly changed with conversion and TOS. A kinetic model capable of describing experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…This catalyst contained only weak acid sites according to ammonia TPD. In addition, 75% selectivity of menthols at 98% citral conversion over 5 wt % Ni/mesoporous aluminosilicate-sepiolite extrudates [Ni/(MAS+sepiolite)] was reported in ref . When comparing the current results with [Ni/(Beta-38+Att.)]…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…This catalyst contained only weak acid sites according to ammonia TPD. In addition, 75% selectivity of menthols at 98% citral conversion over 5 wt % Ni/mesoporous aluminosilicate-sepiolite extrudates [Ni/(MAS+sepiolite)] was reported in ref . When comparing the current results with [Ni/(Beta-38+Att.)]…”
Section: Resultssupporting
confidence: 60%
“…When comparing the current results with [Ni/(Beta-38+Att.)] with 44–45% menthol yields, it can be observed that this catalyst contains a 2.23-fold higher amount of Brønsted acid sites than (Ni/(MAS+sepiolite)). Furthermore, comparing the performance of [Ni/(H-Beta-38+Att.)]…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations